Exploring sequential art in Sarawak : the story of semut in Sarawak - Horn, Christine (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The goal of this project is to cover an interesting episode of local Sarawak history and local cultures and present this in a graphic novel. The story line is based on an important and significant part of local history, which has been adapted to suit the aim of giving an insight of life within the interior of Sarawak sixty years ago, during World War II. The style used draws on that of the western graphic novel tradition, with a strong influence of local impressions. Leading up to this project, extensive research has been conducted in local and international image archives, literary and historical research documents, and importantly primary research while travelling to longhouse, kampongs and forests within Sarawak. The present thesis will serve as outline of the planning, conception and development of the project, to describe some of the difficulties experienced in its progress, the research conducted, and the techniques used in its construction.